Socioeconomic position, psychosocial work environment and cerebrovascular disease among women: the Finnish public sector study - Kivimäki, Mika (Oxford University Press, 2009)
Background The excess risk of fatal and non-fatal cerebrovascular disease in people from low socioeconomic positions is only partially explained by conventional cerebrovascular risk factors. This has led to the suggestion that poor psychosocial work environments provide important additional explanatory power. However, little evidence is available for women. Methods We examined whether job demands or job control contributed to the socioeconomic gradient in cerebrovascular disease among 48 361 women aged 18–65 years. Job demands, job control and behavioural risk factors were self-reported in 2000–2002; socioeconomic position (as indexed by occupational class) and all of the health measures were obtained from registers. The outcome was recorded hospitalization or death from cerebrovascular disease. Results During a mean follow-up of 3.4 years, 124 women had a new cerebrovascular disease event. The risk was 2.3 (95% CI 1.3–3.9) times higher among women in low vs high socioeconomic positions. Adjustment for conventional risk factors, such as prevalent hypertension, coronary heart disease, diabetes, smoking, heavy alcohol consumption, physical inactivity and obesity, attenuated this excess risk by 23%. In contrast, adjustment for job demands and job control actually amplified the gradient by 36% suggesting a suppression effect. Conclusions In this contemporary cohort of employed women, job demands—alone and in combination with job control—suppressed rather than explained socioeconomic differences in cerebrovascular disease.